Pengaruh Manajemen Laba, Leverage dan Intensitas Modal terhadap Agresivitas Pajak Perusahaan pada Perusahaan Food and Beverage yang Terdaftar di Bursa Efek Indonesia - Ishak, Ishak; Akhmad Sadeli, Yudi; Ibrahim, Ibrahim; Charmelitha Mau, Lenny (Al-Buhuts, 2024)
This research aims to determine and analyze the Influence of Earnings Management, Leverage, and Capital Intensity on Corporate Tax Aggressiveness in Food and Beverage Companies Listed on the Indonesia Stock Exchange for the Period 2020 – 2023. By applying the Purposive Sampling method, this research takes the population of financial reports from 95 food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the Period 2020 – 2023. A total of 47 samples were selected for analysis in this study." The research method used in this study is descriptive analysis and multiple linear regression using SPSS 25 as a tool.The results of this study indicate that Earnings Management does not affect Tax Aggressiveness, Leverage has a positive and significant effect on Tax Aggressiveness, and Capital Intensity does not have a significant effect on Tax Aggressiveness.